Influência do ácido hipocloroso obtido a partir de um dispositivo eletrolítico nas propriedades da dentina radicular: estudo in vitro - Farina, Carolina Bianchi (2023)
This study aimed to evaluate, in vitro, the influence of acid hypochlorine obtained through an electrolytic device in the properties of root dentin. One hundred and fifty extracted bovine teeth were used to carry out 5 different evaluations: 30 for microhardness analysis, 15 for flexural strength analysis, 15 for cohesive strength analysis, 60 for analysis of fracture resistance and 30 for analysis of dentin penetration. To the auxiliary chemical substances evaluated were divided into six groups: water deionized, NaOCl 1%, NaOCl 2.5%, NaOCl 5.25%, hypochlorous acid 250 ppm and hypochlorous acid 500 ppm. The results demonstrated that the groups treated with distilled water and hypochlorous acid had no significant difference in microhardness of root dentin (p>0.05). However, groups treated with NaOCl demonstrated significant differences in dentin microhardness (p<0.05). In the mechanical tests it was possible to observe that in the resistance to bending and cohesive strength, the control group and hypochlorous acid did not obtain statistical difference between them (p>0.05). However, the groups with NaOCl demonstrated significant difference (p<0.05), when compared to other substances. Node fracture resistance test, it can be seen that there was no statistical difference between any group tested (p>0.05). And finally, in the dentin penetration test the tested groups were statistically different from the control group (p<0.05), however, without statistically significant differences between them (p> 0.05). One can conclude that hypochlorous acid had no influence on microhardness, as well as in flexural, cohesive and fracture resistance, in addition to presenting satisfactory dentin penetration.